Transient Responses in Nonlinear Dynamics of Structures - Awrejcewicz, Jan (Journal of Applied Nonlinear Dynamics, 2026)
Innumerable mechanical structures including vibrating profiles, sandwich plates, platforms, thin uniperiodic shells, laminated windshells, isotropic and orthotropic platesor even multibody systems exhibit complex dynamic behavior. Analysis of the corresponding phenomena involves interesting mathematical and experimental methods that are sometimes used in parallel. Mostly, a dynamical transient response of any of the enumerated complex structures leads to the unpredictable states that need to be described and predicted. For this reason, the Special Issue extends selected papers presented during the international conference on “Dynamical Systems-Theory and Applications” hold in December 2–5, 2013 in Lódź, Poland. Main areas of modern experimental and numerical analysis taken into consideration by authors of these papers could be mentioned: bifurcations and chaos in dynamical systems, stability of dynamical systems, original numerical methods of vibration analysis, non-smooth systems, engineering systems and differential equations, control in dynamical systems, asymptotic methods in nonlinear dynamics,vibrations of lumped and continuous systems,dynamics in life sciences and bioengineering. A brief description of contents of this Special Issue follows.